Effect of gabapentin on haloperidol induced inhibition of conditioned avoidance response in rat - Bhansali, Nishant B.; Goyal, Yash N.; Divakar, Baluswamy; Mistry, Sureshchandra D.; Chavda, Dinesh A.; Chacko, Jiyo (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Haloperidol, an antipsychotic adversely affects acquisition and retention of a learned task. We decided to test the effect of Gabapentin, a new anti-epileptic drug using conditioned avoidance response model with cook’s pole climbing apparatus and haloperidol. Methods: Four groups of six rats were taken for this purpose. All the rats were first given drugs for five days and then trained for a period of 15 days. Gabapentin was given in a dose of 100mg/kg intra peritoneal, while haloperidol was given 0.5mg/kg intra peritoneal. Results: At the end of the training duration rats in the vehicle and gabapentin treated group achieved ≥85% acquisition responses. While the haloperidol and haloperidol + gabapentin group did not achieve the desired percentage of learning. A learning curve was plotted by using the percentage of conditioned responses in each group versus number of days. The mean ± SD percentage of conditioned responses of day 14 and 15 were for haloperidol group 26.19 ±11.90, for vehicle group 86.90 ± 4.29, for the gabapentin treated group 95.24 ± 2.38 and for the gabapentin + haloperidol group 46.42 ± 12.20. These figures and the learning curve suggest that gabapentin treated rats had a better acquisition response and haloperidol depressed learning. Conclusions: At the end of study duration we found that gabapentin significantly improved the acquisition response than the vehicle control group. Also haloperidol depressed the acquisition response. Gabapentin did not lead to reversal of haloperidol induced depression of acquisition process.